Math, asked by mahanandsah43, 14 days ago

26) Find the product :- 6a + 5b)(7a - 2b)​

Answers

Answered by lavanyarajudp161nv
1

Step-by-step explanation:

(6a+5b ) (7a-2b)

=6a(7a-2b) + 5b(7a-2b)

= 6a(7a) - 6a(2b) + 5b(7a) - 5b(2b)

=42a²- 12ab +35ba - 10b²

=42a² + 23ab - 10b²

Answered by vaishnvaimuthukumar0
0

Answer:

the answer is 39 ab

Step-by-step explanation:

first step:

[6a+5b] [7a-2b]

so we take a and b value separetly

[6a+7a] [5b-2b]

13a x 3b

answer: 39ab

Similar questions